Safety and efficacy of a feed additive consisting of Lacticaseibacillus huelsenbergensis DSM 115424 for all animal species (Lactosan GmbH & Co. KG) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on Lacticaseibacillus huelsenbergensis DSM 115424 when used as a technological additive to improve ensiling of all fresh plant material for all animal species at a proposed minimum concentration of 1 × 108 colony forming units (CFU)/kg fresh plant material. The bacterial species L. huelsenbergensis is considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. The identity of the strain was established, and no acquired antimicrobial resistance genes of concern were detected. Therefore, the FEEDAP Panel concluded that the use of the strain as a silage additive is considered safe for all animal species, for consumers of products from animals fed with the treated silage and for the environment. Regarding user safety, inhalation and dermal exposure are considered a risk. One preparation of the additive containing whey powder as a carrier was shown not to be irritant to skin or eyes. However, the Panel cannot assess the irritation potential of other possible preparations. The FEEDAP Panel concluded that L. huelsenbergensis DSM 115424 has the potential to improve the production of silage prepared from all fresh plant materials at a minimum concentration of 1 × 108 CFU/kg fresh material.